Análisis y diseño de red para comunicación inalámbrica en la Unidad Educativa Salesiana Cardenal Spellman - Alvarez Chamorro, Alex Guillermo (2016)
This paper aims to conduct a study to allow the insertion of standards-based IEEE 802.11network compatible with the diversity of customers Wi-Fi certified at the U.E.S.C.S. Wireless network is established as a supplement to the existing wired network increasing the means of access to the network in the educational institution. Among the objectives of the project is the identification of the radio environment of the area under study, internal and external sources that hinder wireless communications and selection of equipment necessary to enable provide ubiquitous coverage on campus ensuring quality data transmitted from sender to receiver. The results of propagation studies and field studies in the U.E.S.C.S. show that the number of selected equipment provide ubiquitous coverage with wireless presence levels RSSI greater than -70 dBm in remote areas and based on load tests network is expected to have a limit of 60 concurrent users per wireless device. The wireless network design is complemented with a financial analysis reflecting the investment required to implement the solution with the cost-benefit ratio that best fits the requirements of the educational institution.